Serum immunoglobulin free light chain levels in systemic autoimmune rheumatic diseases. (31st October 2019) - Gulli, F.; Napodano, C.; Marino, M.; Ciasca, G.; Pocino, K.; Basile, V.; Visentini, M.; Stefanile, A.; Todi, L.; De Spirito, M.; Rapaccini, G. L.; Basile, U.
Summary: Several reports have highlighted the abnormal increments of serum immunoglobulin free light chains (FLCs) in the course of systemic autoimmune rheumatic diseases (SARD), but a comparative analysis among different conditions is still lacking. A strong association between elevated FLC and hepatitis C virus (HCV)‐related mixed cryoglobulinaemia (HCVMC) has been well established. Here, we aimed to analyse serum FLC levels in patients with four different SARD in comparison with HCVMC. Using a turbidimetric assay, free κ and λ chains were quantified in sera from 198 SARD patients (37 rheumatoid arthritis, RA; 47 systemic lupus erythematosus, SLE; 52 anti‐phospholipid syndrome, APS; 62 primary Sjogren's syndrome, pSS), 62 HCVMC and 50 healthy blood donors (HD). All patient groups showed increased κ levels when compared to HD: 33·5 ± 2·6 mg/l in HCVMC, 26·7 ± 2·3 mg/l in RA, 29·7 ± 1·9 mg/l in SLE, 23·8 ± 1·1 mg/l in APS, 24·2 ± 1·1 mg/l in pSS; 10·1 ± 0·6 mg/l in HD. Free λ levels displayed a significant increase only for HCVMC (20·4 ± 1·4 mg/l) and SLE (18·4 ± 1·0 mg/l) compared to HD (13·6 ± 0·9 mg/l). The increase of κ compared to λ takes into account a κ /λ ratio of 1·6 for all groups. Our results substantially analyse and strengthen the association between FLC and SARD focusing the questions regarding their role in the pathogenesis and diagnosis of human diseases. Unfortunately, the biochemical differences distinguishing normal from pathological FLC have not been identified. Production of different isotypes is probably connected to still‐unknown pathways. Abstract : Our study confirms the occurrence of abnormal increases of immunoglobulin free light chains (FLC) in systemic autoimmune rheumatic diseases (SARD), with a comparative analysis of serum levels in four different disorders. Our results strongly suggest that the addition of FLC analysis in routine panels can improve the quality of laboratory diagnosis, offering physicians a direct viewpoint on B‐cell activation. Based on our data and well‐demonstrated biological properties, we hypothesize the pathogenic potential of FLCs that could act as 'mini autoantibodies'.